Needs assessment to incorporate Saudi human genome project and personalized medicine into saudi undergraduate medical curriculum - Marwa Ahmed El Naggar (Wolters Kluwer Medknow Publications, 2023)
Introduction: The Saudi Human Genome Program (SHGP) is one of the groundbreaking national programs and the largest genome initiative in the Middle East. His Royal Highness has put the growth of the health-care sector at the top of government priorities to ensure and increase the welfare of the Saudi nation. There are a few studies about needs assessment to incorporate the Saudi Human Genome and personalized medicine in Saudi Arabia's medical curricula until now. Aim: This study aimed to assess the need to incorporate Saudi Human Genome theme and personalized medicine into the Saudi undergraduate medical curriculum. Methodology: A cross-sectional descriptive study was implemented and a simple random sample of 28 faculty members and medical educationists working inside KSA was taken. The study followed Kern's six-step approach to curriculum development designed by Kern et al. 2005, by the application of its first four steps: (i) problem identification and general needs assessment, (ii) targeted needs assessment, (iii) goals and objectives, (iv) educational strategies, (v) implementation, and (vi) evaluation and feedback. A self-administered questionnaire was designed on Google Forms and distributed electronically by E-mail and WhatsApp groups to assess faculty members' needs determine course objectives and teaching methods, and level, and determine the departments that will manage it, and students' assessment tools. Results: Twenty-eight medical educationists and faculty members from different specialties participated in the study. 26 (92.9%) and 16 (57.10%) of the study population stated that their undergraduate medical curriculum did not address the topics of the Saudi Human Genome and personalized medicine, respectively. Twenty-two (78.60%) agreed that there is a need to incorporate both topics in the curriculum. Twenty-four (85.70%) agreed that incorporating SHGP will familiarize students with the importance of genetic counseling in reducing and preventing hereditary and genetic diseases. Conclusion: There is a lack of incorporation of the Saudi Human Genome Project and personalized medicine into the Saudi medical curriculum, and there is a need to incorporate both topics into it to gauge its effectiveness and identify areas for its implementation improvement.